2006
DOI: 10.3171/spi.2006.5.5.455
|View full text |Cite
|
Sign up to set email alerts
|

Regression of retroodontoid pseudotumors following C-1 laminoplasty

Abstract: ✓The authors report a new technique for C-1 laminoplasty without fusion in the treatment of cervical myelopathy associated with a retroodontoid pseudotumor (also known as a phantom tumor). The authors review the cases of three patients who underwent C-1 laminoplasty in which hydroxyapatite was used and fusion was not performed. All patients suffered from severe progressive myelopathy before surgery. Magnetic resonance imaging revealed a retroodontoid pseudotumor compressing the spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 9 publications
1
45
0
Order By: Relevance
“…[1][2][3]6,7 The recommended surgical management of ROP is a combination of laminectomy and posterior C1-C2 fixation with transarticular screws, without removal of the ROP. 3,4,9,10 The ROP gradually reduces within 1 year after surgery, as observed in our patient. [3][4][5]11 Differentiation of the retro-odontoid mass is often difficult.…”
Section: Discussionsupporting
confidence: 67%
“…[1][2][3]6,7 The recommended surgical management of ROP is a combination of laminectomy and posterior C1-C2 fixation with transarticular screws, without removal of the ROP. 3,4,9,10 The ROP gradually reduces within 1 year after surgery, as observed in our patient. [3][4][5]11 Differentiation of the retro-odontoid mass is often difficult.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast, Suetsuna et al [14] reported that two of three retro-odontoid pseudotumor patients had spontaneous regression after C1 laminoplasty using hydroxyapatite. In terms of reduction rate, the authors considered that C1 laminectomy seemed inferior to posterior fusion.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, spontaneous regression of pseudotumors following posterior fusion has been reported [10,13]. On the other hand, Suetsuna et al [14] reported spontaneous regression of retro-odontoid pseudotumors following C1 laminoplasty. The etiology of retro-odontoid pseudotumor remains controversial and the appropriate surgical procedure to treat it has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested C1-ring osteosynthesis using C1 lateral mass screws as a surgical intervention for atlas fractures [25,26]. Additionally, Suetsuna et al suggested the effectiveness of C1 laminoplasty as a less invasive surgical procedure without fusion for retro-odontoid pseudotumor [17]. These procedures, which not only preserve the motion segment but also augment disruption of the circular morphology, may be a prophylactic surgical intervention for anterior arch fracture, especially in cases that involve severe bone fragility.…”
Section: Discussionmentioning
confidence: 97%